ACTIVITY REPORT-MN - LANE, WES (Tufts Archival Research Center, 2007)
Confidential; Letter from Wes Lane to Susan Stuntz regarding the July 1991 Activity Report. Reports on the restriction of the sale of cigarettes in two cities, but announces that one of the cities has decided to appoint a committee to look into the issue, rather than pass an ordinance.